1998
DOI: 10.1124/mol.53.4.623
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor-Dependent Suppression by 2,3,7,8-Tetrachlorodibenzo-p-dioxin of IgM Secretion in Activated B Cells

Abstract: The immune system has been identified as a sensitive target for the toxic effects produced by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). Furthermore, the B cell has been identified as a sensitive cellular target of TCDD by previous cell-type fractionation studies from this laboratory. The mechanism responsible for the immunotoxic effects produced by TCDD is unclear; however, many of the biological effects of TCDD are thought to be mediated by the aryl hydrocarbon receptor (AhR). Here, we describe two B cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
83
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 36 publications
9
83
0
Order By: Relevance
“…The fact that TCDD-induced expression of nuclear target genes observed in the present work was highly sensitive to FK506 treatment and CnA mRNA silencing suggests that CnA is involved in these transcriptional responses and in the activation of NF-B. In keeping with this possibility it has been reported that TCDD activates NF-B by AhR-independent mechanisms (40,41).…”
Section: Discussionsupporting
confidence: 70%
“…The fact that TCDD-induced expression of nuclear target genes observed in the present work was highly sensitive to FK506 treatment and CnA mRNA silencing suggests that CnA is involved in these transcriptional responses and in the activation of NF-B. In keeping with this possibility it has been reported that TCDD activates NF-B by AhR-independent mechanisms (40,41).…”
Section: Discussionsupporting
confidence: 70%
“…In experimental systems (animal and in vitro experiments), PCB/dioxin exposure leads to suppression of humoral and cell-mediated immunity and has direct effects on hematopoietic stem cells and B-cell or T-cell differentiation (8,11,36,37). However, the underlying mechanisms for these effects have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The AhR can both induce (Matikainen et al, 2001(Matikainen et al, , 2002Nebert et al, 1991) and suppress gene transcription (Sulentic et al, 1998;Wang et al, 1999Wang et al, , 2001). Therefore, a human c-myc promoter-reporter construct (pGL3-c-myc) was used to determine if constitutive AhR binding to the c-myc promoter effects an increase or decrease of c-myc levels.…”
Section: Ahre-dependent Regulation Of the C-myc Promotermentioning
confidence: 99%
“…AhR-dependent upregulation of these enzymes results in increased metabolism of some AhR ligands such as PAH and the production of carcinogenic intermediates (Buters et al, 1999;Dertinger et al, 2001). In other cases, activation of the AhR results in transcriptional inhibition of genes such as those encoding the immunoglobulin heavy-chain (Sulentic et al, 2000) and estrogen-inducible p27, cathepsin D, and pS2 (Safe et al, 1998;Porter et al, 2001).…”
Section: Introductionmentioning
confidence: 99%